HISTORY LEARNING THROUGH THE PROJECT-BASED LEARNING METHOD AT SMAN 1 DEMPET, GRADE XI, ACADEMIC YEAR 2025/2026: Pembelajaran Sejarah dengan Metode Project Based Learning di SMAN 1 Dempet kelas XI tahun Pelajaran 2025/2026 - Nugraha putra dahlan Tama; Romadi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to describe the implementation of Project-Based Learning in history instruction at SMAN 1 Dempet, identify the challenges encountered, and analyze the solutions implemented by the teacher. The study employed a qualitative approach using a case study method. The participants consisted of one history teacher and three eleventh-grade students selected through purposive sampling. Data were collected through semi-structured interviews and documentation, then analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings indicate that the implementation of Project-Based Learning enhances students' participation, understanding of the subject matter, and engagement in the learning process. The study concludes that Project-Based Learning is an effective instructional method for improving the quality of history education while fostering students' active participation and learning motivation.